USER INTERFACE DESIGN FOR INSTAGRAM SOCIAL MEDIA APP INTERACTION - zulhamdani zulhamdani; Muhammad Azwir Badawi; Asril Abdi Harahap; Supina Batubara (Journal of Information Technology, computer science and Electrical Engineering, 2024)
User interface (UI) design plays a crucial role in the user experience on social media applications. Instagram, as one of the largest social media platforms, has set high standards when it comes to inspiring and aesthetic UIs. The study aims to analyze the UI design elements on Instagram that contribute to user satisfaction and comfort. This study examines aspects such as layout, navigation, design consistency, use of iconography, color schemes, and application responsiveness. The methods used include descriptive analysis of Instagram UI components, user satisfaction surveys, and usability teststo identify potential areas for improvement. The results of the study show that the Instagram user interface is designed with a focus on ease of navigation, simplicity, and high visual consistency. The use of recognizable icons and attractive color schemes helps enhance the visual experience and make it easier for users to interact User surveys show high satisfaction levels related to the accessibility of key features such as photo/video uploads, content browsing through feeds and Stories, and social interaction through comments and direct messages. However, the study also found several areas that are can be improved, such as optimizing the display on devices with various screen sizes and improving personalization features for the user experience. Overall, Instagram's UI design managed to create a positive user experience through a user-centric design approach. The findings of this study are expected to provide insights for designers and developers of social media applications in creating smooth.